Damage detection in structures using a transmissibility‐based Mahalanobis distance. Issue 10 (27th February 2015) - Zhou, Yun‐Lai; Figueiredo, E.; Maia, N.; Sampaio, R.; Perera, R.
Summary In this paper, a damage‐detection approach using the Mahalanobis distance with structural forced dynamic response data, in the form of transmissibility, is proposed. Transmissibility, as a damage‐sensitive feature, varies in accordance with the damage level. Besides, Mahalanobis distance can distinguish the damaged structural state condition from the undamaged one by condensing the baseline data. For comparison reasons, the Mahalanobis distance results using transmissibility are compared with those using frequency response functions. The experiment results reveal quite a significant capacity for damage detection, and the comparison between the use of transmissibility and frequency response functions shows that, in both cases, the different damage scenarios could be well detected. Copyright © 2015 John Wiley & Sons, Ltd.